Rethinking the Language Use within a Countryto Trace the Evidence of LinguisticUniversality - Sudirman, A. M.; Ninsiana, W. (Advances in Social Sciences Research Journal, 2017)
Language phenomena and dialects (in a country) may have not been studied and described comprehensively to provide adequate answers. The method used in this study is descriptive research method with data collection techniques obtained from various sources, all research techniques that complement each other. Data were collected and analyzed and followed by data selection, compilation / classification and summary, these were conducted in an integrated manner. The method used in this study is descriptive research methodology with data collection techniques obtained from various sources that are in complement to each other. The data were collected and analyzed and followed by data selection process, compiled / classified and summarized in an integrated manner. Based on the description of the language ecology as common happens in a country wherein there is at least a foreign language (FL), the national language (NL), and the local language (LL)'; In a country there maybe possible occurs two or more bilingual communication. In the language contact we usually know the status of isolects they use. The status of a person's isolects could be as FL, NL, and LL. In other words, the isolated form of a language is a complement of the language they speak. Thus, the status of isolates in a language or a dialect used in formal situations can be demonstrated in the user's situation and its use properly and correctly as a reflection of a language use.